Analyzing chronic dream ego responses in co-creative dream analysis - Sparrow, Gregory Scott (International Journal of Dream Research, 2014)
With the advent of the co-creative dream paradigm, which is based on the principle that dreams are indeterminate from the outset, and co-created through the reciprocal exchanges between the ego and emergent dream content, the analysis of the dreamer’s responses becomes an important new dimension in dream analysis. In this paper, the author develops the hypothesis that chronic dream ego responses can be traced to two sources in the individual’s prior experience: 1) trauma and loss, and 2) introjected parental and cultural ideals. The individual’s efforts to prevent trauma and loss from recurring accounts for “reactive adaptive responses,” and attempts to emulate introjected ideals results in “compliant adaptive responses.” Both of these types of chronic responses can be identified with the dreamer’s help in dream analysis, and facilitative alternatives can be formulated in dialogue with the dreamer. The author presents a sequence of steps that can be used as a standalone method, or incorporated into existing dream work